1998
DOI: 10.1111/j.1600-0722.1998.tb02181.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the (DSS)n triplet repeat domain of rat dentin phosphophoryn

Abstract: Properties of the (DSS)., triplet repeat domain of rat dentin phosphophory11. Eur J Oral Sci 1998; 106 (suppl I ): 234 238. ·c,;, Eur J Oral Sci, 1998 Pho~phophoryns (PPs) are unique aspartic acid and phosphoserine-rich proteins present in a ll species of dentin. R at incisor odontoblast eDNA libraries contain messages encod ing severa l acidic phosphorylated. serine-rich proteins. At least two of these share a common C-terminal domain cod ing region sequence. The polypeptide seq uences in the N-te1minal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
29
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 2 publications
5
29
0
Order By: Relevance
“…1B). This antibody (a gift from Dr. A. Veis) has been previously shown to have cross-reactivity with phosphophoryn due to the common content of (DSS) n repeats (19,20). We confirmed the correct size and migration of the recombinant PP through Western blot analysis (Fig.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…1B). This antibody (a gift from Dr. A. Veis) has been previously shown to have cross-reactivity with phosphophoryn due to the common content of (DSS) n repeats (19,20). We confirmed the correct size and migration of the recombinant PP through Western blot analysis (Fig.…”
Section: Resultssupporting
confidence: 60%
“…The precipitated proteins from the medium and cell/matrix were either further purified by column chromatography, or blotted on nitrocellulose paper using dot blot or Western blot techniques using both the anti-PP antibody (generated in our laboratory) and the antidentin matrix protein 2 (DMP2) antibody (a generous gift from Dr. Arthur Veis, Northwestern University). This antibody has been previously shown to have cross-reactivity with phosphophoryn due to the common content of (DSS) n repeats (19,20). As a positive control, we used our recombinant PP as well as recombinant DMP2, provided by Dr. Veis.…”
Section: Transfection Of Pshooter-er-pp Construct Into Mc3t3-e1 and Nmentioning
confidence: 99%
“…In situ hybridization experiments have shown that DMP-1 is expressed by hypertrophic chondrocytes, osteoblasts, and odontoblasts (28). Another dentin ECM protein, phosphophoryn (PP), a cleavage product of DSPP (16), has been implicated as a regulator of mineral crystal formation (16,18,19,29). DSPP is localized to chromosome 4, linking mutations in the gene to dentinogenesis imperfecta type II (15,16).…”
mentioning
confidence: 99%
“…Odontoblasts secrete PP along the mineralization front (21,37,38) and, typical of other NCPs, the physiochemical properties of PP dictate high affinity for Ca 2ϩ , which implicates a role in the nucleation or modulation of HA crystal formation (13,22,24). An RGD domain is present at the N-terminal domain of PP (13,19), suggesting an auxiliary function in ECM-cell communication and in the initiation of intracellular signaling pathways. PP, like DMP-1, is a SIB-LING protein family member and could have an important regulatory role in osteogenic signaling and growth factor activity.…”
mentioning
confidence: 99%
“…PP is localized in dentin and bone and is a regulator of matrix mineralization (27). PP is highly negatively charged and consists of many repeats of Asp-Ser-Ser (DSS) n , where n could be as high as 28 (28). Our recent work has demonstrated that PP activates many of the same target genes as BMP-2, including Runx2, Osx, alkaline phosphatase (Alp), and osteocalcin (Ocn) (1).…”
mentioning
confidence: 99%